التحليل الوراثي للغلة وبعض مكوناتها في بعض أصناف البازلاء الخضراء (Pisum sativum L.) - خوجة حسان; غنيم عفيف; العايش فراس (Latakia University Journal -Biological Sciences Series, 2018)
نفذت الدراسة في مركز بحوث درعا التابع للهيئة العامة للبحوث العلمية الزراعية بدمشق وفق تصميم القطاعات العشوائية الكاملة بثلاث مكررات خلال ثلاثة مواسم متتالية 2003/2004 ، 2004/2005 و2005/2006 لتقييم أداء الهجن نصف التبادلية الناتجة من توظيف تصميم التهجين نصف المتبادل بين ستة طرز وراثية من البازلاء الخضراء بهدف دراسة مقدرة الائتلاف العامة والخاصة وقوة الهجين قياساً لمتوسط وأفضل الأبوين لصفات الغلّة وبعض مكوّناتها. أظهرت النتائج سيادة التباينات العائدة لمقدرة الائتلاف الخاصة على تباينات مقدرة الائتلاف العامة لصفتي عدد الفروع المثمرة على النبات وعدد البذور في القرن ، مما يعكس سيطرة الفعل الوراثي غير الإضافي في توريث هذه الصفات في الهجن نصف التبادلية وبالتالي فإن تلك الصفات واقعةً تحت تأثير جينات السيادة الفائقة ، في حين كان الفعل الوراثي الإضافي هو السائد لصفتي عدد القرون على النبات وغلة النبات الواحد من القرون الخضراء ، مما يعني خضوع هذه الصفات لتأثير جينات السيادة الجزئية. The present investigation was conducted at Center of Daraa Research, General Commission for Scientific Agricultural Research in Damascus, using randomized complete blocks design with three replications, during three successive seasons 2003/2004, 2004/2005 and 2005/2006. It tried to evaluate the performance of half-diallel hybrids resulting from employing half-diallel crossing system among six genotypes of garden peas. The main objective was to study both the general and specific combining ability and mid and better-parents heterosis of some yield and yield components. Results revealed the dominance of variances of specific combining ability of a number of productive branches per plant and the number of seeds per pod, indicating importance of non-additive gene action. Therefore, these traits were affected by the over-dominance gene effect, while the additive gene action was predominant for two traits based on the number of pods per plant and the yield of green pods per plant. This means that the last two characters were affected by partial-dominance gene effect.